(3fhQ GdYjhf aj PcQ LQLG ef YgO KdGKI bQhfs - (3eMeO Hf eMeO Hf MGeO Hf eMeO GdLQLGhj GdeQGZj,J (B1355 (3g` s
(3ChdgG (B:s
(3CeG HYO deG aQZJ ef cJGHi JYWjQ GdfhGMi hGdCQLG HPcQ ef GTJgQ ef YdeGA hCYjGf eOjfI GdUYjO LQLG hbO hbaJ GdGf Ydi eGJQLeg HYV GdeDQNjf s
(3BNQgG (B:s
(3hCHhGdaVd gPG gh GdYdGeI GdTjN CHhGdaV eMeO GdSeghOi, eaJi GdSGOI GdTGaYjI HLQLG s
(3HBNQgG hbajI cGJHg hagQSJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B204s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B463 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs